THE EFFECT OF CELERY LEAF EXTRACT (APIUM GRAVEOLENS L.) ON TNF-Α, IL-6 AND MDA LEVELS IN HYPERPIGMENTED WISTAR RATS (RATTUS NOVERGIUS SP.) - Dina R. Purba; Jekson M. Siahaan; Endy Juli Anto; Syafruddin Ilyas; Hadyanto L (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The objective of this study was to evaluate the anti-inflammatory effects of Celery leaf extract (Apium graveolens L.) on hyperpigmented Wistar rats (Rattus norvegicus sp.) induced by Azidothymidine (AZT). Celery leaves are known to contain bioactive compounds which may serve as potent anti-inflammatory and antioxidant agents. About 30 male Wistar rats were divided into five groups, including a positive control, a negative control, and groups treated with various doses (1%, 3% and 5%) of celery leaf extract. The study examined inflammation indicators such as MDA, TNF-α, and IL-6. Celery leaf extract significantly (P<0.001) reduced MDA, TNF-α, and IL-6 levels in rats, demonstrating its capacity to attenuate inflammation and oxidative stress produced by AZT. With the increase in celery leaf extract concentration from 1% to 5%, MDA, IL-6 and TNF-α levels decreased from 42.083 ± 3.49 to 28.277 ± 10.27 nmol/ml, 14.588 ± 3.38 to 4.539 ± 1.40 nmol/ml and 667.614 ± 143.41 to 326.920 ± 62.72 nmol/ml respectively. Histopathological examinations demonstrated improvements in skin tissues damaged by inflammation. The results indicate that an ethanol extract of celery leaves has the potential to be an efficient anti-inflammatory drug, notably in lowering AZT-induced inflammation and hyperpigmentation. Further research is required to explore its clinical applicability in controlling inflammatory diseases in human.